2020
DOI: 10.1111/coep.12483
|View full text |Cite
|
Sign up to set email alerts
|

The Mortality Cost of Expenditures

Abstract: This paper updates the mortality cost of expenditures, which has relevance to a broad range of policies, including regulations, wars, and COVID-19 restrictions. Because changes in income lead to changes in mortality risk, health investments costing more per life saved than a threshold cost-per-life-saved cutoff level are expected to increase mortality risk. This article discusses the mechanisms driving this relationship and provides recent empirical support. The 2019 cost-per-life-saved cutoff level at which e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 41 publications
0
19
1
Order By: Relevance
“…The mechanism driving this effect is that economic costs reduce expenditures made by households to reduce risk privately. A recent estimate suggests that for every $111 million (in 2020 dollars) in reduced income, one expected death will occur [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism driving this effect is that economic costs reduce expenditures made by households to reduce risk privately. A recent estimate suggests that for every $111 million (in 2020 dollars) in reduced income, one expected death will occur [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, a production metric must account for the fact that resources that are consumed have an opportunity cost. An important opportunity cost of lost production is the alternative use of resources to address other mortality risks [ 10 ], which is an opportunity cost explicity accounted for in this paper.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sacrificing a large share of wealth to reduce mortality risk from a particular hazard (e.g., SARS-CoV-2) could lead to impoverishment and increases in other mortality risks. Health and longevity are positively correlated with income and wealth and there is a literature that estimates how decreases in income increase total mortality risk based on cross-sectional and longitudinal data (Wildavsky 1979(Wildavsky , 1980Keeney 1990Keeney , 1997Hariharan 1994, 1996;Broughel and Viscusi 2020). Viscusi (1994a, b) showed that the rate at which a marginal reduction of income increases mortality risk equals VSL divided by the individual's marginal propensity to spend on mortality-risk reduction; he estimated this marginal propensity as roughly 0.1, which suggests the effect of paying v(δ) to reduce a particular risk by δ reduces total mortality risk by only 0.9 δ.…”
Section: Valuing Non-marginal Risk Reductionmentioning
confidence: 99%
“…Comprehensive assessments of the mortality cost also should include the mortality costs that are associated with a loss in income. Based on the conceptual approach in Viscusi (1994) coupled with recent empirical estimates in Broughel and Viscusi (2021), a loss in income of just over $100 million will lead to one expected death based on a VSL of $10 million. This relationship highlights the important link between the performance of the economy and individual health.…”
Section: Mortality and Morbidity Effectsmentioning
confidence: 99%